Understanding Pore Surface Modification of Sucrose-Modified Iron Oxide/Silica Mesoporous Composite for Degradation of Methylene Blue - Yuvita Eka Pertiwi; Maria Ulfa; Teguh Endah Saraswati; Didik Prasetyoko; Wega Trisunaryanti (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Santa Barbara Amorphous (SBA-15) containing iron oxide with a sucrose-modified in a heterogeneous reaction for degradation methylene blue (MB) successful synthesized used hydrothermal, ultrasonication, and wet impregnation method. SBA-15 is mesoporous silica that can easily serve as external and internal surfaces making it suitable for a wide range of applications. The structure and morphology of materials were characterized using Surface Area Analyzer (SAA), X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX), and Transmission Electron Microscopy (TEM). Iron oxide impregnated as a maghemite phase has an average size of 12 nm and well distributed on the SBA-15. After modified with sucrose the materials remaining stable, which has a two-dimensional hexagonal (p6mm) structure, high specific surface area, and large pore volume (up to 1.82 cm3.g−1). The degradation of MB was evaluated under visible light irradiation using UV-Vis spectroscopy. Catalytic activity showed efficiencies of 52.9; 70.2; and 21.1% for SBA-15, Fe2O3/SBA-15, and sucrose-modified Fe2O3/SBA-15 respectively. Sucrose-modified Fe2O3/SBA-15 has the lowest efficiency, which probably occurs due to the presence of pore-blocking and the formation of micropores on the external pore. The modification with sucrose has the advantage of producing a high surface area even though there is a catalytic center due to partial decomposition which causes a decrease in the efficiency of degradation of MB. All materials provide a high micro surface area so that they can be further adapted and can be widely applied to many potential applications as both catalyst support and an adsorbent. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).